Práticas Reflexivas Com IA No Design: Desenvolvendo Agência Criativa Em Contexto Bicultura - Mortensen Steagall, Marcos (Universidade do Estado de Minas Gerais (UEMG), 2025)
This article investigates how communication design students develop critical awareness when integrating artificial intelligence (AI) tools into their creative processes. Based on three years of ethnographic observation (2022- 2024) in a final-year undergraduate design studio in New Zealand, the study documents pedagogical approaches that position AI as a situated tool within broader design practices. Objective: to demonstrate that systematic reflective practices enable emerging designers to maintain creative agency and cultural sensitivity when working with AI technologies. Methodology: action research with 87 students through structured workshops, process documentation, and longitudinal comparative analysis. Results: students participating in reflective workshops demonstrated significantly greater capacity (85% versus 41%) to recognise when AI suggestions diverged from culturally informed intentions, particularly within a bicultural educational context informed by Te Tiriti o Waitangi and Māori epistemologies.
Keywords: 330316 Visual communication design (incl. graphic design); 3303 Design